2009
DOI: 10.4314/jasem.v10i2.43664
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Intestinal Worm (Helminthiasis) infestation in a Central Nigerian Rural Community

Abstract: ABSTRACT:The prevalence of intestinal helminth of residents of Naraguta rural community in Central Nigeria is presented. Out of 700 stool specimens examined between January and July 1999, 261 (37.3%) were positive for helminthic infections. Helminths encountered include Hookworm, Schistosoma mansoni, Trichuris trichiura, Strongyloides stercoralis, Ascaris lumbricoides, and Hymenolepis nana. Hookworm was the most predominant, followed by S. stercoralis, S. mansoni and A. lumbricoides with T. trichiura as the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 1 publication
4
9
1
Order By: Relevance
“…The difference in the prevalence may be due to geographical variations and season of the study, varying in tick availability. Similar results were obtained by Edosomwan & Chinweba (2012), who recorded prevalence of 28.0% in Benin City, Southern Nigeria while working on normal house- Anosike et al (2006) in rural community in central Nigeria, 34.8% by Ramirez-Barrios et al (2004) in Venezuela. However, the prevalence was lower than the 62.7%, obtained by Ogunkoya et al (2006) in Zaria, 93.8% observed by Umar, (2009) in Kaduna metropolis, 52.6% by Okoye et al (2011) in South-easthern Nigeria, and 59.3% by Swai et al (2010) in Tanzania.…”
Section: Discussionsupporting
confidence: 88%
“…The difference in the prevalence may be due to geographical variations and season of the study, varying in tick availability. Similar results were obtained by Edosomwan & Chinweba (2012), who recorded prevalence of 28.0% in Benin City, Southern Nigeria while working on normal house- Anosike et al (2006) in rural community in central Nigeria, 34.8% by Ramirez-Barrios et al (2004) in Venezuela. However, the prevalence was lower than the 62.7%, obtained by Ogunkoya et al (2006) in Zaria, 93.8% observed by Umar, (2009) in Kaduna metropolis, 52.6% by Okoye et al (2011) in South-easthern Nigeria, and 59.3% by Swai et al (2010) in Tanzania.…”
Section: Discussionsupporting
confidence: 88%
“…Fresh stools are sometimes used as fertilizer and may contain viable eggs and larvae (Kouontchou et al, 2002). However, a related study in a rural community in central Nigeria found that T. trichiura was significantly lower than other parasites encountered, with hookworm being the most prevalent, followed by A. lumbricoides (Anosike et al, 2006). Ascaris lumbricoides showed the highest prevalence, followed by T. trichiura and least by hookworms.…”
Section: Introductionmentioning
confidence: 89%
“…[22][23] The prevalence rate of helminthiasis (20.2%) observed among the HIV negative children in this study was within the range of prevalence rates of helminthiasis in Nigerian children (9.1% to 95.7%). [24][25][26] The pattern of helminthiasis among study participants showed that children above 12 years of age (post-primary school age) had the lowest prevalence rate of helminthiasis in both subjects and controls. This agreed with that reported by Wagbatsoma et al, [16] who also observed the least prevalence of helminthiasis in children above primary school age.…”
Section: Discussionmentioning
confidence: 99%